Bortezomib-Induced Acute Pancreatitis - Elouni, Bouraoui; Salem, Chaker Ben; Zamy, Michelle; Sakhri, Jaballah; Bouraoui, Kamel; Biour, Michel (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Illustration of the proteasome inhibitor bortezomib bound to an assembled yeast proteasome core (PDB ID 2F16). (Author: Opabinia regalis; Wikimedia Commons)